Piety Consumption Among Urban Muslim Youth at The Teras Dakwah Community in Yogyakarta - Saputra, Eko; Lyansari, Kirana Nur (Mafapress - Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) IPMAFA Pati, 2025)
The contemporary da’wa social movement has catalyzed transformative shifts in religious practices. Da’wa no longer confined to Islamic political advocacy, revivalist agendas, or moral panics, da’wa now intersects with the commodification of faith, merging Islamic identity with pop culture and market-driven trends. This evolution has redefined religious engagement, prioritizing the symbolic appropriation of popular culture to appeal to modern audiences. Methodologically, this study employs an ethnographic field research approach, focusing on the Muslim youth community associated with Teras Dakwah Community in Yogyakarta. The findings reveal that market-oriented religious practices have fostered consumerist tendencies, exemplified by the commercialization of Islamic fashion, the redesign of da’wa study spaces into café-like environments, and the rebranding of preaching venues as social hubs for youth. Consequently, da’wa culture has transitioned into a hybrid space where religious discourse coexists with pop aesthetics, reflecting broader societal shifts toward the commodification of spirituality. This article clearly explains Schielke's argument that piety consumption is not something that can be avoided, as it is an adaptation to the condition of being a Muslim in the modern era.